Voice of the Margin in Literature: Reading Arundhati Roy’s The Ministry of Utmost Happiness - Bhusal, Tilak (Lumbini Journal of Language and Literature, 2022)
This research article is an attempt to explore the humiliated condition of transgender in Roy’s The Ministry of Utmost Happiness. The humiliation made on different people in the society by the upper class people has been depicted in the novel. Roy has presented the discrimination faced by the different people in a subtle way. The injustice over the Hindu people in India and the marginalized Muslim and the conflict among them has been portrayed artistically. The novel presents the dark side of an Indian society in the modern history. She upholds the rights of voiceless people and attempts to raise their voice which could be heard around the globe.